2021
DOI: 10.1080/21655979.2021.2003676
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin ameliorates chronic stress-induced depression-like behavior in mice model by affecting ERK1/2 pathway

Abstract: Depression is a mental and emotional disorder that has made an opening great burden to the society. Paeoniflorin showed remarkable antidepressant-like effects in multiple animal models with depressive disorders. However, the molecule of paeoniflorin on depression is less studied. This study aims to explore the effect and the molecular mechanism of paeoniflorin on depression in a chronic restraint stress (CRS) mice model. CRS model of C57BL/6 J mice was set up. Sucrose preference test (SPT), tail suspension tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…A series of studies indicated that the target of antidepressant drugs was determined by using inhibitors 40,41 . For example, previous studies showed that the antidepressant‐like actions of paeoniflorin, geniposide, and curcumin were blocked by using U0126, LY94002, and SR18292, which identified ERK, PI3K, and PGC‐1α as the targets of the above drugs, respectively 42–44 . This study also used a similar method to diagnose whether TrkB could be used as the antidepressant target of loganin by using the recognized TrkB inhibitor K252a in CUMS‐induced depression–like mice.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A series of studies indicated that the target of antidepressant drugs was determined by using inhibitors 40,41 . For example, previous studies showed that the antidepressant‐like actions of paeoniflorin, geniposide, and curcumin were blocked by using U0126, LY94002, and SR18292, which identified ERK, PI3K, and PGC‐1α as the targets of the above drugs, respectively 42–44 . This study also used a similar method to diagnose whether TrkB could be used as the antidepressant target of loganin by using the recognized TrkB inhibitor K252a in CUMS‐induced depression–like mice.…”
Section: Discussionmentioning
confidence: 97%
“…40,41 For example, previous studies showed that the antidepressant-like actions of paeoniflorin, geniposide, and curcumin were blocked by using U0126, LY94002, and SR18292, which identified ERK, PI3K, and PGC-1α as the targets of the above drugs, respectively. [42][43][44] This study also used a similar method to diagnose whether TrkB could be used as the antidepressant target of loganin by using the recognized TrkB inhibitor K252a in CUMS-induced depression-like mice. In this study, behavioral results displayed that 10 and 20 mg/kg loganin significantly reversed the decrease of sucrose intake in SPT induced by CUMS, while K252a blocked the antidepressant-like actions of loganin, suggesting that TrkB might be a target for the antidepressant-like actions of loganin.…”
Section: Discussionmentioning
confidence: 99%
“…All of them presented potential pharmacological mechanisms. Of these, Paeoniflorin possibly plays a neuroprotective effect in improving chronic stress-induced depression and neuronal damage in rats through activation of the ERK-CREB pathway [ 26 , 27 ]. Studies have shown that albiflorin directs antidepressant role by the cytoplasmic phospholipase A2 (cPLA2) -protein kinase B (Akt1)-indoleamine 2,3-dioxidase 1(IDO1) regulatory loop [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Icariin (ICA) is a flavonoid glucoside isolated from Epimedium brevicornu Maxim , which is frequently used in traditional Chinese medicine (TCM) to treat asthma [19], kidney disease [20], testicular dysfunction [21] and cartilage damage [22]. TCM is often used to treat depression, for example, paeoniflorin improves chronic stress-induced depression behavior in mice model by influencing the ERK1/2 pathway [23]. Zhang et al revealed that Xiaoyao powder can reduce the damage of hippocampal neurons in CUMS-induced hippocampal depression model rats through connexin 43Cx43/GR/brain-derived neurotrophic factor signaling pathway [24].…”
Section: Introductionmentioning
confidence: 99%